ANALISA DAN PERANCANGAN APLIKASI PEMANTAU TUMBUH KEMBANG ANAK DENGAN METODE BODY MASS INDEX BERBASIS WEB - Arif Wahyudi Suryanto; Ratna Mutu Manikam (Jurnal Ilmiah FIFO, 2021)
Health is the most important thing in life. Especially for the first five years of age of children. The growth and development of children in the first five years of age are very vulnerable and need more supervision from parents. However, many parents do not pay attention and ignore the health and development and development of toddlers, due to reasons too busy or lack of facilities or containers that support the supervision activities. With the rapid development of technology today, it can simplify and help daily activities, including activities to monitor children's growth and development. This research tries to design a web-based application that can facilitate parents in monitoring children's growth and development. This study used the method of developing the Waterfall system and PIECES. In this application there is an information system for calculating a child's ideal body weight using the body mass index method, calculating the measurement of the framework, as well as searching for a child's poly location specifically in the DKI Jakarta area. This web-based child growth and development application will help parents in monitoring children's growth and development as well as finding the location of children's poly in DKI Jakarta